2013
DOI: 10.1371/journal.pone.0053650
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Plant CYP51s Confers Resistance against Voriconazole, a Novel Inhibitor of Brassinosteroid-Dependent Sterol Biosynthesis

Abstract: Brassinosteroids (BRs) are plant steroid hormones with structural similarity to mammalian sex steroids and ecdysteroids from insects. The BRs are synthesized from sterols and are essential regulators of cell division, cell elongation and cell differentiation. In this work we show that voriconazole, an antifungal therapeutic drug used in human and veterinary medicine, severely impairs plant growth by inhibiting sterol-14α-demethylation and thereby interfering with BR production. The plant growth regulatory prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“…Voriconazole, an inhibitor of P450 in plants ( Rozhon et al, 2013 ), did not show any effect on P. tricornutum growth even at 105 μg/ml, which is about 300-fold the concentration of effective doses for most land plants ( Rozhon et al, 2013 ). Therefore, this antibiotic was not investigated further.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Voriconazole, an inhibitor of P450 in plants ( Rozhon et al, 2013 ), did not show any effect on P. tricornutum growth even at 105 μg/ml, which is about 300-fold the concentration of effective doses for most land plants ( Rozhon et al, 2013 ). Therefore, this antibiotic was not investigated further.…”
Section: Resultsmentioning
confidence: 88%
“…Accordingly, we tested the efficiency of the antibiotics by cultivating P. tricornutum cells on plates containing different concentrations of antibiotics. According to previous publications, a lethal dose of blasticidin-S of about two μg/ml was reported for mammalian cells ( Izumi et al, 1991 ), for tunicamycin the LD 50 was reported between 0.1 and five μg/ml ( Elbein, 1981 ), while voriconazole at 0.35 μg/ml impaired plant growth ( Rozhon et al, 2013 ). For our experiments, we used concentrations ranges from higher to lower than these values ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…During a recent study, we observed that treatment with voriconazole, a chemical that reduces sterol and BR contents (Rozhon et al, 2013), also reduced levels of the GA GA 34 in wild-type Arabidopsis (results in ng/g dry weight of two measured samples: untreated control: 7.7/ 7.7; + inhibitor: 0.1/ 0.2). To investigate if a deficiency in BRs may result in reduced GA levels we measured GA 4 , which is the major bioactive GA in Arabidopsis (Talon et al, 1990), in 14-d-old seedlings of the BR biosynthetic mutant constitutive photomorphogenesis and dwarfism (cpd; Szekeres et al, 1996) and the two BR signalingdeficient lines bri1-1 (Clouse et al, 1996) and ASKuoe (Rozhon et al, 2010) by gas chromatography-mass spectrometry.…”
Section: Ga Biosynthesis Is Severely Compromised In Br-deficient Mutantsmentioning
confidence: 94%
“…They are nitrogen-containing heterocyclic compounds that form an effective class of fungicides by non-competitively binding to the ferric ion of the heme group of fungal CYP51, thus preventing it from binding its substrate (Rogerson et al, 1977; Warrilow et al, 2013). Despite being primarily used as fungicides, several azole compounds also have an effect on plants to a varying degree, where they generally cause growth inhibition, which may be due to interference with downstream BR biosynthesis (Scheinpflug and Kuck, 1987; Vanden Bossche et al, 1987; Rozhon et al, 2013; Fabris et al, 2014). However, while nanomolar concentrations of azoles are usually sufficient to inhibit ergosterol biosynthesis in fungi, micromolar concentrations or higher are often needed to obtain a similar inhibitory effect on phytosterol biosynthesis in plants and diatoms (Vanden Bossche et al, 1987; Fabris et al, 2014).…”
Section: Chemical Inhibitors Of Key Steps In the Plant Sterol Biosyntmentioning
confidence: 99%